2021
DOI: 10.2217/fmb-2021-0272
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Hospital Discharge Outcome from Changes in Cerebrospinal Fluid/serum Albumin Quotient and Cerebrospinal Fluid Lactate Dehydrogenase in Patients with Cryptococcal meningitis

Abstract: Aim: This study aims to provide reliable prognostic factors for patients with cryptococcal meningitis (CM). Patients & methods: Clinical characteristics and laboratory findings of CM patients were retrospectively reviewed. Results: Sixty-three patients with CM were enrolled and 38/63 were confirmed to be HIV serology positive. Among clinical characteristics, headache, nausea and/or vomiting, and fever were the most common symptoms. Among cerebrospinal fluid (CSF) parameters, changes in leukocyte count, lac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Besides the alteration in the CNS glucose metabolism, the lactate metabolism in the CNS must also be considered. Previous studies have demonstrated that abnormal lactate metabolism in patients with CM brain are closely related to poor prognosis and can also lead to serious consequences such as abnormal mental state, seizures, and significant increase in intracranial pressure [ 46 , 64 , 65 ]. In this study, higher levels of CSF-LDH were observed in the SDB group, which suggested that the abnormal lactate metabolism of the CNS may be related to the structural damage of the brain.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the alteration in the CNS glucose metabolism, the lactate metabolism in the CNS must also be considered. Previous studies have demonstrated that abnormal lactate metabolism in patients with CM brain are closely related to poor prognosis and can also lead to serious consequences such as abnormal mental state, seizures, and significant increase in intracranial pressure [ 46 , 64 , 65 ]. In this study, higher levels of CSF-LDH were observed in the SDB group, which suggested that the abnormal lactate metabolism of the CNS may be related to the structural damage of the brain.…”
Section: Discussionmentioning
confidence: 99%